Sectoral dynamics of financial co-integration between BRICS and developed stock markets - Lima, Roland Nubiga (Department of Finance and Tax, 2020)
This study examines the sectoral dynamics of co-integration between the BRICS (Brazil, Russia, India China and South Africa) and developed stock markets, represented by Germany, Japan, the UK and the US, during the four phases of the Global Financial Crisis (GFC), the three phases of the European Sovereign Debt Crisis (ESDC) and the UK Brexit crisis. The sample includes daily sectoral equity indices over the period January 2006 to December 2017. The study applies the ADCC GJRGARCH model to estimate the time-varying correlations across the nine countries within each sector and across sectors within each country, and assesses the conditional correlation dynamics during each of the phases of the three crisis periods. The results support the existence of financial co-integration across sectors and among all the nine countries during the GFC and ESDC. Only developed countries exhibit co-integration during the UK Brexit crisis. While some sectors were less affected during some of the crisis periods, on average, financials were the most affected during the GFC, ESDC and UK Brexit crisis. Further analysis on a crisis phase level reveals that most country pairs and sector pairs exhibit significant increases in conditional correlations in phase two of the GFC and ESDC, limiting the effectiveness of international diversification during this period. The results provide useful insights for policy makers and investors.